Control of base flows with micro jet for area ratio of 6.25 - Ali Baig, Maughal Ahmed; Khan, Sher Afghan; C., Ahmed Saleel; Rathakrishnan, Ethirajan (Asian Research Publishing Network (ARPN), 2012)
Suddenly expanded flow with active controls in the form of micro jets has been investigated experimentally, laying emphasis on the effectiveness of micro jets on the base pressure and enlarged duct pressure field. Air injection at four locations at the base, symmetric to the nozzle axis is used as the active control. The jet Mach numbers of the present studies are 1.87, 2.2 and 2.58. The area ratio of present study is 6.25. The length-to-diameter ratio of the suddenly expanded duct and the Nozzle Pressure Ratio (NPR) are varied from 10 to 1 and 3 to 11. In addition to base pressure, wall pressure field along the duct was also studied. It is found that the active control in the form of blowing through small orifices (micro jets) are effective in controlling the base pressure field. Micro jets do not augment the flow field in the duct. As high as 55 percent, increase in base pressure was achieved for certain combination of parameters of the present study.